Bramkarka, architektka, polityczka... Kilka uwag o polsko-czeskich analogiach językowych (na przykładzie nazw zawodowych kobiet) - Dembska, Katarzyna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2013)
The article describes the problem of Polish feminine occupational titles in comparison with Czech language. Titles of women’s occupations in the feminine gender can be referred to the model standard in the case of Czech, in which they appear on a regular basis. In the Polish language the current state of knowledge allows for placing such designations within the functional standard, with the reservation that some of them (for example, those connected with sport) are already treated as the model standard. This paper is devoted to the spheres in which feminine forms of the titles of occupations followed by women exist. These include sports, arts, prestigious positions in the public administration as well as in the economy and politics; the army, science and higher education, and the Church. The problem of the linguistic standard and the role of the media in forming the contemporary language are a significant element in the discussion. Hence, the Polish and Czech press texts are the major sources of the research material, whereas lexicographical studies and electronic linguistic corpora facilitate the attempts at verifying the status of particular titles.
Keywords: Polish and Czech feminine occupational titles; feminine forms; Polish and Czech press texts; Grice’s Maxims